Software Development Hour with Sam Newman. (O'Reilly Media, Inc., 2023)
The best time to get started with cybersecurity is now. And the best way to get started is as a team. Join Sam Newman and SafeStack founder and CEO Laura Bell for a special conversation on cybersecurity. They'll discuss why, more than ever, it's crucial that organizations big and small take whatever steps they can to keep their data, people, and systems safe. They'll also explore how secure engineering practices have evolved and what that implies for the future. This is a chance for you to hear from Sam and Laura about software development, cybersecurity, and their own career journeys. They'll spend a few minutes covering the trends that are influencing software, then tell you what you need to know to stay ahead of the curve. What you'll learn and how you can apply it Learn what really matters for software design Find out what's coming next for software development This recording of a live event is for you because... You want the chance to hear from Sam Newman and Laura Bell your about software development. Recommended follow-up: Listen to The Manager's Path (audiobook) Read Building Microservices, second edition (book) Read Security as Code (book).